PELATIHAN PEMBUATAN LILIN AROMATERAPI DENGAN MEMANFAATKAN MINYAK JELANTAH BAGI SISWA MA AL-QODIRI KELIR BANYUWANGI - Moh nurman bagus satrio; Qurrata A’yun; Reny Eka Evi Susanti; Rika Endara Safitri; Rosyid Ridho; Eko Malis; Dimas Priagung Banar Syah (Jurnal Mitra Dedikasi Masyarakat, 2026)
Students today rarely apply the classroom materials they have learned to their daily lives. One of the topics taught at the Senior High School (SMA/MA) level is candle making. Training on producing aromatherapy candles using waste cooking oil can boost students' enthusiasm for practicing school materials. This training session was conducted over one day in partnership with Madrasah Aliyah (MA) Al Qodiri Kelir, Banyuwangi. The methods employed in this training included lectures, Q&A sessions, and hands-on mentoring. The program covered several key areas: the excitement of learning chemistry, an introduction to chemical-based products, the benefits of repurposing waste cooking oil for aromatherapy candles, and direct guidance in the candle-making process. As a result, the training successfully increased students' awareness of the environmental hazards posed by waste cooking oil and equipped them with the practical skills to create aromatherapy candle products from recycled oil.